PENGGUNAAN KONJUNGSI KOORDINATIF DALAM NOVEL KASIH TAK TERLERAI KARYA SOEMAN HS - Misrawati '; Mangatur sinaga; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRAK:This research is to describe useing coordinative conjunction in a novel Kasih Tak Terlerai created by Soeman HS. The aim of this research is to know and to discribe about using coordinative conjunction in a novel Kasih Tak Terlerai created by Soeman HS. This research is about descriptive qualitative. The source of this research is a novel Kasih Tak Terlerai created by Soeman HS consist of 11 sub tittle. The result of this research refer to formulation and the aim of research. Frist data be fount as much as 172 be found using coordinative conjunction in the first as much as16, using coordinative conjunction in the middle is as 152, and using coordinative conjunction in the end is nothing. Using coordinative conjunction whic connecting klausa by clausa as much as 152, and conecting sentence by sentence as much as 16 data. Second, the meaning of this novel Kasih Tak Terlerai created by Soeman HS as much as 15 meaning that is (1) quantity meaning (and) sequences meaning (then and past), selection meaning (or) opposite meaning (buts, however, while, butrather and but) and meaning more (moreover).Key words: coordinative conjunction, quantity meaning, sequences selection, apposite and more over meaning